2021
DOI: 10.1039/d0cp06257j
|View full text |Cite
|
Sign up to set email alerts
|

CO2methanation mechanism over Ni/Y2O3: anin situdiffuse reflectance infrared Fourier transform spectroscopic study

Abstract: Supported Ni catalysts are active in CO2 methanation. To understand the reaction mechanism is important for the development of highly-active catalysts. In this study, we investigated the reaction pathways of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…[44][45][46] Table 2 outlines all the main adsorbates, their vibration modes, and corresponding wavenumbers. [32,[44][45][46][47][48][49][50][51][52][53][54][55][56] The most significant difference is observed for Ni/Al 2 O 3 -500/ 800, which also shows peaks at 2017 and 1885 cm À 1 . We assign these peaks to linear and bridged CO adsorbed on the surface of metallic Ni, respectively.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…[44][45][46] Table 2 outlines all the main adsorbates, their vibration modes, and corresponding wavenumbers. [32,[44][45][46][47][48][49][50][51][52][53][54][55][56] The most significant difference is observed for Ni/Al 2 O 3 -500/ 800, which also shows peaks at 2017 and 1885 cm À 1 . We assign these peaks to linear and bridged CO adsorbed on the surface of metallic Ni, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, the catalyst formed no bicarbonate or carbonate species under the same reaction conditions. [61] Lastly, it is worth noticing that a band at 1618 cm À 1 appears in the ME-PSD-DRIFTS of Ni/Al 2 O 3 -500/800, which is associated with the OÀ H bending mode of H 2 O in the interlayer of the catalyst. [62] The exact peak location was determined from the phase domain trace plot in Figure S9 (plotted in phase angles of ϕ = 360°/12).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Two main reaction pathways for CO 2 methanation have been proposed: associative and dissociative of CO 2 molecules. , The associative mechanism involved CO 2 associative bonds with adsorbed H atom to produce formate, followed by hydrogenation of formate to CH 4 (Figure a). The dissociative mechanism proposed that CO 2 would dissociate on the catalyst surface with CO as an intermediate (Figure b), followed by hydrogenation. , It was also found that formate and CO could be generated on one kind of catalyst with different reaction conditions (Figure c). , In addition, both formate and CO routes can be observed at the same condition for some catalysts, e.g., Ni/Ce 0.8 Zr 0.2 O 2 and Ni/Y 2 O 3 catalysts.…”
Section: Introductionmentioning
confidence: 91%
“…As the 2-EHA/ RE 3+ ratio increases, the peak of NO 3 − persists but is not as sharp as before, and the increasing content of 2-EHA will lead to the emergence of the vibration absorption of carbonyl (CO) at ∼1530 cm −1 . 28,29 The gradually intensifying vibration absorption of CO will increase the phonon energy of the particles, which may be sufficient to quench the intensities of the UCL bands.…”
Section: Structure and Morphologymentioning
confidence: 99%